Genders In Speed Reading; A Comparative Study At The Forth Semester Students In Faculty Of Culture, Management, And Business Language Education Mandalika University Of Education - Terasne, Terasne; Setianingsih, Tri (Lembaga Penelitian dan Pendidikan Mandala, 2021)
Genders in Speed Reading; A Comparative Study at the Forth Semester Students in Faculty of Culture, Management, and Business, Language Education, This study aimed to compare male and female students’ ability in speed reading. The population of this study were the forth semester students at Faculty of Culture, Management, and Business, Language Education Mandalika University of Education in academic year 2020/2021. There were 60 students as the sample of the study in which divided into class IVA for male consisted of 30 students and class IVB for female consisted of 30 students. Data was collected by using timed reading. The data were analyzed and interpreted statistically by using a comparative method. They study found that both students ability in speed reading male and female, was bad. They are very slow readers. The data showed 11 out of 30 male students (37%) are categorized to be low readers and-19 out of 30 male students (63%) was categorized as very slow readers. Similarly 8 out of 30 female students (27%) were categorized as low readers and 22 out of 30 female students (73%) are categorized as very slow readers. There were no significant differences between genders in speed reading. The study shows the t-test value 0.298 was lower than t-table values of 2.000 at confidence level 95% and 2.660 at confidence level 99%.